A Reform of the Security Council through the Expansion of its Relations with other Bodies and Organizations - Kholoud Mohamed Bamegdad (International Journal of Law Research and Studies, 2025)
This study explores the reform of the UN Security Council through the expansion of its relations with other bodies and organizations. The current international context has highlighted the urgent need for such reform, given the Security Council’s role in maintaining international peace and security. The reality discovers the need to address the Council’s reform from multiple perspectives, particularly by expanding its relations and operations through reconsidering its interactions with other UN bodies to ensure the adoption of impartial and effective decisions. Additionally, strengthening the relationship with regional organizations is essential to enhance their role in preserving international peace and security. The study aims to identify one of the key aspects limiting the Council’s effectiveness. It discusses the need to activate the Council’s relations with the General Assembly, the importance of controlling the misuse of its broad powers, and the nature of cooperation with regional organizations. Solutions are proposed to improve collaboration in addressing international crises. The study is divided into two sections: the first focuses on activating the Security Council’s relationship with UN bodies, offering reform solutions at the General Assembly level and activating oversight over Council’s decisions. The second section addresses enhancing cooperation with regional organizations by clarifying the nature of their relationship and proposing reforms to strengthen this cooperation. Using a descriptive-analytical approach, the study concludes that oversight is crucial for ensuring respect for international law and enhancing the Council’s credibility. It also emphasizes the importance of reorganizing the relationship between the Security Council and regional organizations to activate cooperation, strengthening the regional role in addressing threats to international peace and security. This is in line with the requirements of collective security. The study recommends enhancing regional organizations’ advisory role, monitoring the implementation of Council decisions, and contributing to resolving regional conflicts.